ROLE OF LEADER IN EDUCATIONAL MANAGEMENT: Received: 25th March 2023; Revised: 3rd April 2023, 28th July 2023; Accepted: 2nd August 2023 - Chkheidze, Salome (PUPIL: International Journal of Teaching, Education and Learning, 2023)
The main objective of this article is to describe a role of leader and define its importance in educational management. The role of a leader in educational management is critically important to make the educational institution provide high-quality education to students, to create an effective management system and motivate the staff to go towards the aim (Eacott, 2015). On the educational context, leadership influences the process, which finally leads to the achievement of desired purpose. A good leader should develop a vision on values of their educational institutions on personal and professional sides. A successful leader makes the staff love their job and be determined to achieve success. Educational leadership is a process, where a leader takes the initiative to facilitate the following conditions for implementing change in teaching and learning (Surya, 2011). The leader in educational leadership is responsible for setting the vision and mission of the educational institution, which serves as a guiding principle for all stakeholders, including students, teachers, and staff. Moreover, the leader must ensure that the educational institution environment is conducive to learning, which includes creating a safe and respectful atmosphere for students and teachers.